Angel or devil: the dual roles of 2,3,5,4′-tetrahydroxystilbene-2-O-β-D-glucopyranoside in the development of liver injury based on integrating pharmacological techniques: a systematic review - Jiang, Jiajie; Wang, Qixiu; Wu, Qiang; Deng, Bobin; Guo, Cui; Chen, Jie; Zeng, Jinhao; Guo, Yaoguang; Ma, Xiao (Frontiers in Pharmacology, 2025)
Background and purpose2,3,5,4′-tetrahydroxystilbene-2-O-β-D-glucoside (TSG) exhibits a dualistic pharmacological profile, acting as both a hepatoprotective and hepatotoxic agent, which is intricately linked to its interaction with multiple signaling pathways and its stereoisomeric forms, namely, cis-SG and trans-SG. The purpose of this study is to evaluate both the hepatoprotective and hepatotoxic effects of TSG and give therapeutic guidance.MethodsThis study performed a systematic search of eight databases to identify preclinical literature up until March 2024. The CAMARADES system evaluated evidence quality and bias. STATA and Python were used for statistical analysis, including dose-effect maps, 3D maps and radar charts to show the dose-time-effect relationship of TSG on hepatoprotection and hepatotoxicity.ResultsAfter a rigorous screening process, a total of 24 studies encompassing 564 rodents were selected for inclusion in this study. The findings revealed that TSG exhibited bidirectional effects on the levels of ALT and AST, while also regulating the levels of ALT, AST, TNF-α, IL-6, serum TG, serum TC, SOD, MDA, IFN-γ, and apoptosis rate. The histological analysis of liver tissue confirmed the regulatory effects of TSG, and a comprehensive analysis revealed the optimal protective dosage range was 27.27–38.81 mg/kg/d and the optimal toxic dosage range was 51.93–76.07 mg/kg/d. TSG exerts the dual effects on liver injury (LI) through the network of Keap1/Nrf2/HO-1/NQO1, NF-κB, PPAR, PI3K/Akt, JAK/STAT and TGF-β pathways.ConclusionTSG could mediate the pathways of oxidation, inflammation, and metabolism to result in hepatoprotection (27.27–38.81 mg/kg/d) and hepatotoxicity (51.93–76.07 mg/kg/d).